The honey queen - Kelly, Cathy (HarperCollins, 2013)
It's easy to fall in love with the beautiful town of Redstone - the locals wave and chat to each other, the shops are full of cheerful hustle and bustle. And amidst all this activity, two women believe they are getting on just fine. Francesca takes everything in her stride, including a husband whose lost his job and the onset of menopause. Peggy, approaching 30, has opened her own knitting shop on the town's high street. It's a dream come true, but she still feels adrift. When Australian-raised Lillie finally makes it back home to Ireland, she's drawn right into the heart of Redstone's thriving community, and all of her hard-earned wisdom will be called into play as she helps new friends navigate unchartered territory